2002
DOI: 10.1103/physrevb.65.193106
|View full text |Cite
|
Sign up to set email alerts
|

Description of exchange and correlation in the strongly inhomogeneous electron gas using a nonlocal density functional

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…It has recently been shown that non-local functionals [19,20] such as the weighted density approximation can be used to accurately calculate the structure of the XC holes in real materials which allows for a fuller understanding of their electronic properties from a fundamental viewpoint. Such an example is shown in Fig.…”
Section: Non-local Exchange and Correlationmentioning
confidence: 99%
“…It has recently been shown that non-local functionals [19,20] such as the weighted density approximation can be used to accurately calculate the structure of the XC holes in real materials which allows for a fuller understanding of their electronic properties from a fundamental viewpoint. Such an example is shown in Fig.…”
Section: Non-local Exchange and Correlationmentioning
confidence: 99%
“…There has been significant interest in the weighted density approximation [61,62], mostly in condensed matter physics [50][51][52][53]57,[63][64][65][66][67], but also for the study of surfaces [58,[68][69][70][71] and metal clusters [49,72].…”
Section: Weighted Density Approximation (Wda)mentioning
confidence: 99%
“…First, the WDA XC potential has the correct −1/r asymptotic behaviour for finite systems [13]. Second, the WDA is designed to capture effects due to the inhomogeneity of the electron densities [40][41][42], where the LDA/GGA is not well defined. Finally, although they do not cancel exactly, the self-interaction errors are much smaller than in the case of LDA/GGA.…”
Section: Theorymentioning
confidence: 99%